Renal effects of novel antiretroviral drugs - Milburn, James; Jones, Rachael; Levy, Jeremy B. (Nephrology, dialysis, transplantation, 2017)
Chronic kidney disease (CKD) is a critical comorbidity for patients living with HIV, with an estimated prevalence between 2.4 and 17%. Such patients are increasingly affected by diseases associated with ageing, including cardiovascular disease and CKD, and the prevalence of risk factors such as smoking and dyslipidaemia is increased in this population. Proteinuria is also now recognized as a common finding in individuals living with HIV. While combination antiretroviral (ARV) treatments reduce CKD in the HIV-infected population overall, some ARV drugs have been shown to be nephrotoxic and associated with worsening renal function. Over the last few years, several highly efficacious new ARV agents have been introduced. This brief review will look at the novel agents dolutegravir, raltegravir, elvitegravir, cobicistat, tenofovir alafenamide fumarate and atazanavir, all of which have been licensed relatively recently, and describe issues relevant to renal function, creatinine handling and potential nephrotoxicity. Given the prevalence of CKD, the wide range of possible interactions between HIV, ARV therapy, CKD and its treatments, nephrologists need to be aware of these newer agents and their possible effect on kidneys.